Higher-order income risk over the business cycle - Christopher Busch; Alexander Ludwig (International Economic Review, 2024)
We explore the consequences of higher-order risk in a standard incomplete-markets life-cycle model. We calibrate the model using a canonical income process with persistent and transitory risk, extended to feature cyclical shock distributions with left-skewness and excess kurtosis. We estimate this income process for U.S. household data, and find shocks to be highly leptokurtic, with countercyclical variance and procyclical skewness of persistent shocks. In the model, first, higher-order risk has sizable welfare implications; second, it matters quantitatively for the welfare costs of cyclical idiosyncratic risk; third, it has nontrivial implications for self-insurance against~shocks.
Keywords: 330